0064 The Odp Takes The Lead. (1st November 2014) - Rimmer, Neil; Parr, Tim; Schofield, Louise
Abstract : Background: Simulation in healthcare is continuing to gain popularity and is recognised in anaesthesia as an invaluable method of teaching anaesthetists both non-technical and technical skills. 1 Evidence of similar training for Operating Department Practitioners (ODPs) is lacking. We designed and piloted a unique multidisciplinary high fidelity simulation course aimed at teaching student ODPs clinical skills and human factors. Methodology: This course took place in situ in the theatre complex. Six high fidelity scenarios were designed with specific learning objectives. These included; local anaesthetic toxicity, high spinal, anaphylaxis and malignant hyperpyrexia. Key learning objectives included early recognition of an emergency and the importance of communication during critical incidents. Results: Ten student ODPS participated in this pilot course. They were given a questionnaire pre and post course with questions related to the course, and a few generic anaesthetic questions thrown in. The mean pre course questionnaire score was 46% (11%–63%) and this improved to 94% (84%–100%) following the course. All students rated the course as 'excellent', and all students felt 'more confident' when dealing with anaesthetic emergencies after the course. Potential impact: There was a 48% improvement in questionnaire results, which would suggest that the students had learnt from the scenarios. Our next step is to regularly carry out this course for all student ODPs rotating through this hospital and to map this specifically to the University syllabus. Reference: Weller J, Wilson L, Robinson B. Survey of change in practice following simulation-based training in crisis management. Anaesthesia, 2003;58(5):471–473